The Market for Remittance Services in Southern Africa - World Bank Group (World Bank, Washington, DC, 2018)
Remittances are an important source of income for households in the Southern African Development Community (SADC), as well as a crucial source of foreign exchange for countries in the region. Despite the relatively large inflows of remittances to SADC, the cost of sending money to and within the region is significantly higher than other regions in the world. To address the high cost of remittances globally, the World Bank has been involved in a number of initiatives aimed at improving the efficiency and safety of the market for remittances. At the regional level, the SADC Committee of Central Bank Governors (CCBG) has led several initiatives aimed at enhancing the regional payment system infrastructure, also with a focus on reducing the cost of remittances within the region.